PRRSV Promotes MARC-145 Cells Entry Into S Phase of the Cell Cycle to Facilitate Viral Replication via Degradation of p21 by nsp11 - Wen, Xuexia; Ge, Xinna; Zhou, Lei; Zhang, Yongning; Guo, Xin; Yang, Hanchun (Frontiers in Veterinary Science, 2021)
Porcine reproductive and respiratory syndrome virus (PRRSV) remains one of the most economically significant pathogens that seriously affect the global swine industry. Despite sustained efforts, the factors that affect PRRSV replication in host cells are far from being fully elucidated and thus warrants further investigation. In this study, we first demonstrated that PRRSV infection can cause downregulation of endogenous p21 protein in MARC-145 cells in a virus dose-dependent manner. Next, we analyzed the effect of p21 knockdown by RNA interference on cell cycle progression using flow cytometric analysis, and found that knockdown of p21 promotes MARC-145 cells entry into S phase of the cell cycle. Interestingly, we further discovered PRRSV infection is also able to promote MARC-145 cells entry into the S phase. Subsequently, we synchronized MARC-145 cells into G0/G1, S and G2/M phases, respectively, and then determined PRRSV replication in these cells. Results here show that the MARC-145 cells synchronized into the S phase exhibited the highest viral titer among the cells synchronized to different phases. Additionally, to reliably analyze the potential role of endogenous p21 protein in PRRSV replication, we constructed a p21 gene-knockout MARC-145 cell line (p21-/-) using CRISPR/Cas9 technology and evaluated its capability to support PRRSV replication. Our results indicate that knockout of p21 is conducive to PRRSV replication in MARC-145 cells. Furthermore, through construction of a series of eukaryotic plasmids expressing each of individual PRRSV proteins combined with cell transfection, we demonstrated that the nonstructural protein 11 (nsp11) of PRRSV mediates p21 degradation, which was further confirmed by generating a stable MARC-145 cell line constitutively expressing nsp11 using a lentivirus system. Notably, we further demonstrated that the endoribonuclease activity rather than the deubiquitinating activity of nsp11 is essential for p21 degradation via mutagenic analysis. Finally, we demonstrated that nsp11 mediates p21 degradation via a ubiquitin-independent proteasomal degradation manner. Altogether, our study not only uncovers a new pathogenesis of PRRSV, but also provides new insights into development of novel antiviral strategies.